Selling Pain to the Saturated Self - Scott, Rebecca; Cayla, Julien; Cova, Bernard (Journal of Consumer Research, 2017)
AbstractHow can we comprehend people who pay for an experience marketed as painful? On one hand, consumers spend billions of dollars every year to alleviate different kinds of pain. On the other hand, millions of individuals participate in extremely painful leisure pursuits. In trying to understand this conundrum, we ethnographically study a popular adventure challenge where participants subject themselves to electric shocks, fire, and freezing water. Through sensory intensification, pain brings the body into sharp focus, allowing individuals to rediscover their corporeality. In addition, painful extraordinary experiences operate as regenerative escapes from the self. By flooding the consciousness with gnawing unpleasantness, pain provides a temporary relief from the burdens of self-awareness. Finally, when leaving marks and wounds, pain helps consumers create the story of a fulfilled life. In a context of decreased physicality, market operators play a major role in selling pain to the saturated selves of knowledge workers, who use pain as a way to simultaneously escape reflexivity and craft their life narrative.